Analisis Penggunaan Kalimat Aktif dan Kalimat Pasif pada Rubrik Pendidikan kompas.com Bulan September 2024 - Ismi Wahyuningsih; Siti Aisyah; Asep Purwo Yudi Utomo; Fatimatuz Zahra; Eri Marsa Dwi Septiana; Amilia Buana Dewi Islamy; Dwi Setiyawan (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This research analyzes active and passive sentences in the education rubric on the kompas.com website in September 2024. This research aims to describe active and passive sentences based on type, structure, and characteristics in online news text. The method used in this study is a theoretical and methodological approach. The theoretical approach is in the form of syntax, while the methodological approach is in the form of qualitative descriptive with data collection techniques of observing and recording. The data collected comes from primary and secondary data through literature studies. The use of qualitative descriptive methods is intended to analyze active and passive sentences in the education rubric on the kompas.com website. The data analysis technique is the agih technique with formal and informal presentations. The results of this study are the discovery of the use of active and passive sentences in news texts with an education theme on the kompas.com website. The research results are detailed by classifying active and passive sentences and describing their structure and type. The benefits of conducting this research are increasing insight and knowledge regarding active and passive sentences and their types, structures, and characteristics in their use in online news texts.